(3HYV efHFGJ GdJOHQ GdPGJj GdaYGd dOi eQVi GdfhY GdKGfj ef GdScQj aj GdchjJ (B= s Some predictors of effective patient self-management with type-2 diabetes in Kuwait - (3JZQjO SdjeGf SfO GdTWjs; (3ajUd YHOGdbGOQ jhfS (B: s ((3GdbGgQI (B: s (3JZQjO SdjeGf SfO GdTWj (B: s, 2012)
(3JgOa gPg GdOQGSI Edi GcJTGa eOi CgejI YOO ef GdeJZjQGJ GdeSJbdI (B((3CYQGV GdfhY GdKGfj ef GdScQj(B: (3GdeYJbOGJ fMh GdScQj(B: (3h fhYjI GdMjGI GdeJYdbI HeQV GdScQj(B: (3h GdGcJFGH(B: (3h GdQVG Yf GdYdGL(B: (3h GdLfS GdHjhdhLj(B) (3aj GdbjeI GdJfHDjI GdOGdI HGSJLGHGJ CaQGO GdYjfI Ydi GdeJZjQ GdJGHY (B((3GdJOHQ GdPGJi deQV GdScQj(B) (3dOi eQVi GdfhY GdKGfi ef GdScQi aj GdchjJ(B: (3h eG EPG cGfJ gfGc aQhb Hjf GdLfSjf aj Jdc GdeJZjQGJ(B. (3h bO CLQjJ OQGSI JegjOjI ddJMbb ef GdcaGAI GdbjGSjI ddebGjjS GdeYQHI h cPdc OQGSI CSGSjI Ydi YjfI CNQi ef GdQGTOjf bhGegG (B((3223(B) (3ef eQVi GdfhY GdKGfi ef GdScQi GdeTNUjf Hg(B: (3HhGbY (B((3107 PchQ h 116 CfKj(B) (3ef GdchjJjjf GdeJQOOjf Ydi YjGOGJ GdScQj ai eSJTa eHGQc GdcHjQ HefWbI GdLGHQjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe Yde GdfaSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CYQGV GdfhY GdKGfj ef GdScQjs; (3GdJOHQ GdPGJjs; (3GdfhY GdKGfj ef eQV GdScQjs